A polysaccharide-coated nano-liquid composite mineral and a preparation method and application thereof

CN122911077APending Publication Date: 2026-10-16JIANGSU NANNONG GAOKE ANIMAL PHARMA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611260709.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有包被技术多采用油脂、树脂、蜡质等高分子材料作为包被层,产品为固体颗粒或微丸,其主要目的在于隔离胃酸、实现肠道定向缓释,但包被材料水溶性差,产品无法溶解于水中用于饮水给药;少数以多糖为配体的螯合型产品(如壳聚糖、褐藻多糖螯合微量元素),其制备过程涉及有机溶剂体系、醇沉、喷雾干燥等复杂工序,最终产品仍以干燥粉末为主,工艺能耗高、生产成本高,且同样难以满足饮水添加需求

Benefits of technology

本发明通过超声分散纳米化处理,将复合微量元素制成平均粒径20~100nm的纳米颗粒,比表面积大、在水溶液中分散均匀;结合水溶性多糖包被层的靶向递送作用,可显著提高微量元素在畜禽肠道的吸收效率,吸收利用率可达60%以上,远高于传统无机微量元素10%~25%的吸收率,从而在等量添加的前提下减少微量元素用量,降低养殖成本;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122911077A_ABST
    Figure CN122911077A_ABST
Patent Text Reader

Abstract

The application provides a polysaccharide-coated nano liquid composite mineral and a preparation method and application thereof, which comprises a nano composite trace element core and a polysaccharide coating layer, and is a water-soluble liquid system as a whole; the raw material components are as follows in percentage by mass: 3-15% of composite trace elements, 2-10% of coating polysaccharide, 1-5% of a cosolvent, and the balance of deionized water; the composite trace elements are a combination of water-soluble inorganic salts of two or more of iron, zinc, copper, manganese, selenium and cobalt. The application has a reasonable design, the composite trace elements are processed into nanoparticles with an average particle size of 20-100 nm through ultrasonic dispersion nanocrystallization treatment, the nanoparticles have a large specific surface area and are uniformly dispersed in an aqueous solution; in combination with the targeted delivery effect of the water-soluble polysaccharide coating layer, the absorption efficiency of the trace elements in the intestinal tract of livestock and poultry can be significantly improved, the absorption utilization rate can reach more than 60%, which is much higher than the absorption rate of 10-25% of traditional inorganic trace elements, so that the amount of trace elements is reduced under the premise of equal addition, and the breeding cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention mainly relates to the field of polysaccharide-coated nano-liquid composite minerals, specifically to a polysaccharide-coated nano-liquid composite mineral, its preparation method, and its application. Background Technology

[0002] Trace elements (iron, zinc, copper, manganese, selenium, cobalt, etc.) are essential nutrients for animal growth, development, reproduction, immune regulation, skeletal development, and eggshell formation. They directly participate in the formation and metabolic regulation of hemoglobin and various metalloenzymes, and have a decisive impact on livestock and poultry production performance. Peripartum sows (late gestation to lactation) are in a period of heightened physiological stress, and trace element supply directly affects fetal development, lactation performance, postpartum feed intake, and weaned piglet survival rate. Commercial laying hens have a high demand for trace elements during peak egg production, and their absorption and utilization directly affect egg production rate, eggshell strength, and the stability of the laying cycle. Therefore, the method of trace element supplementation and absorption efficiency are key factors determining the economic benefits of livestock farming.

[0003] During the operation of specific embodiments, the inventors discovered the following defects: Existing coating technologies mostly use polymeric materials such as oils, resins, and waxes as coating layers, and the products are solid particles or microcapsules. Their main purpose is to isolate gastric acid and achieve targeted sustained release in the intestine. However, the coating materials have poor water solubility, and the products cannot be dissolved in water for drinking water administration. A few chelation products with polysaccharides as ligands (such as chitosan and brown algae polysaccharides chelating trace elements) involve complex processes such as organic solvent systems, alcohol precipitation, and spray drying. The final products are still mainly dry powders, with high energy consumption and high production costs, and they are also difficult to meet the needs of drinking water addition.

[0004] It should be noted that the above content falls within the scope of the inventor's technical knowledge. Due to the vast and complex nature of the technical content in this field, the above content of this application does not necessarily constitute prior art. Summary of the Invention

[0005] 1. The technical problem that the invention aims to solve: This invention provides a polysaccharide-coated nano-liquid composite mineral, its preparation method, and its application, in order to solve the technical problems existing in the background art.

[0006] 2. Technical Solution: To achieve the above objectives, the technical solution provided by the present invention is: a polysaccharide-coated nano-liquid composite mineral, characterized in that it is composed of a nano-composite trace element core and a polysaccharide coating layer, and the whole is a water-soluble liquid system; By mass percentage, the raw material components are: 3%–15% complex trace elements, 2%–10% coated polysaccharides, 1%–5% cosolvent, and the balance being deionized water; The composite trace elements are a combination of two or more water-soluble inorganic salts from iron, zinc, copper, manganese, selenium, and cobalt. The coated polysaccharide is one or more of water-soluble plant polysaccharides and microbial polysaccharides.

[0007] Furthermore, the polysaccharide-coated nano-liquid composite mineral is a nanoscale water-soluble liquid system with an average particle size of 20–100 nm, a pH value of 5.0–7.5, and exhibits no stratification or precipitation after 30 days of storage at room temperature.

[0008] Furthermore, the water-soluble plant polysaccharide is one or more of the following: glucan, astragalus polysaccharide, wolfberry polysaccharide, seaweed polysaccharide, and pectin; The microbial polysaccharide is one or more of xanthan gum, yeast polysaccharide, and β-glucan.

[0009] Furthermore, the proportions of each component of the composite trace element are as follows: 10-30 parts iron, 8-25 parts zinc, 1-8 parts copper, 5-20 parts manganese, 0.1-1 parts selenium, and 0.1-0.8 parts cobalt.

[0010] Furthermore, the co-solvent is one or more of propylene glycol, glycerol, and anhydrous ethanol.

[0011] A method for preparing a polysaccharide-coated nano-liquid composite mineral according to any one of the claims, characterized in that it comprises the following steps: Step 1: Preparation and nano-sizing of trace element mother liquor: The water-soluble inorganic salts corresponding to the composite trace elements are added to deionized water in the order of iron salt, zinc salt, copper salt, manganese salt, selenium salt and cobalt salt, stirred until completely dissolved, and then subjected to ultrasonic dispersion and nano-sizing treatment to obtain nano-trace element mother liquor. Step 2: Polysaccharide swelling and dissolution: Add the coated polysaccharide to deionized water, heat in a water bath and stir to allow the polysaccharide to fully swell and completely dissolve, resulting in a polysaccharide solution; Step 3: In-situ coating at constant temperature: Keep the polysaccharide solution at a constant temperature and keep stirring. Add the nano-trace element mother liquor obtained in Step 1 to the polysaccharide solution at a constant rate. After the addition is complete, continue stirring at a constant temperature to complete the polysaccharide coating and obtain the coated mixture. Step 4: Preparation and pH adjustment: Add a co-solvent to the coating mixture, stir and mix evenly, adjust the pH of the system to 5.0-7.5, add deionized water to make up the volume, and stir and mix evenly; Step 5: Filtration and sterilization: Vacuum filtration and sterilization are performed using a 0.22μm aqueous microporous filter membrane. The filtrate is then filled into containers to obtain the polysaccharide-coated nano-liquid composite mineral.

[0012] Further, in step 1, the stirring speed is 200 to 250 r / min, and the stirring time is 15 to 25 min; the ultrasonic power for ultrasonic dispersion nanocrystallization treatment is 200 to 300 W, an intermittent mode is adopted with 3 s of ultrasound and 2 s of pause, and the total treatment time is 20 to 40 min; In step 2, the water bath heating temperature is 40 to 50°C, the stirring speed is 250 to 300 r / min, and the stirring time is 30 to 60 min; In step 3, the holding temperature of the polysaccharide solution is 35 to 45°C, the stirring speed is 300 to 350 r / min, the dropping rate of the nano trace element mother liquor is 8 to 12 mL / min, and after the dropping is completed, the constant-temperature stirring reaction is continued for 40 to 70 min; In step 4, the cosolvent is stirred and mixed for 10 to 15 min, the pH of the system is adjusted to 5.0 to 7.5, deionized water is added to make up the constant volume, followed by stirring for 15 min.

[0013] Further, in step 1, the iron salt is ferrous sulfate, the zinc salt is zinc sulfate, the copper salt is copper sulfate, the manganese salt is manganese sulfate, the selenium salt is sodium selenite, and the cobalt salt is cobalt chloride.

[0014] Further, steps 2 to 4 are all carried out in a clean workshop, with an ambient temperature of 20 to 28°C and a relative humidity of 40% to 65%.

[0015] An application of the polysaccharide-coated nano-liquid composite mineral according to any one of the preceding items in livestock and poultry breeding, characterized in that the application objects are perinatal sows and / or commercial laying hens, and the usage method is adding to drinking water or spraying and mixing on the feed surface.

[0016] 3. Beneficial effects: Adopting the technical solution provided by the present invention, compared with the prior art, the following beneficial effects are achieved: Through the ultrasonic dispersion nanocrystallization treatment, the composite trace elements are made into nanoparticles with an average particle size of 20 to 100 nm, which have a large specific surface area and are uniformly dispersed in an aqueous solution; combined with the targeted delivery effect of the water-soluble polysaccharide coating layer, the absorption efficiency of trace elements in the intestinal tract of livestock and poultry can be significantly improved, the absorption and utilization rate can reach more than 60%, which is much higher than the 10% to 25% absorption rate of traditional inorganic trace elements, thereby reducing the amount of trace elements added under the premise of equal addition and lowering breeding costs; Water-soluble polysaccharides are used to in situ coat the cores of nano-trace elements, forming a polysaccharide coating layer that physically isolates different trace elements such as iron, zinc, copper, manganese, selenium, and cobalt. This avoids chemical reactions and transport competition and mutual antagonism between various metal ions when they coexist in aqueous solution, allowing each trace element to work synergistically to supplement the other elements. At the same time, the polysaccharide coating layer can neutralize the acidic stimulation of free metal ions, protect the intestinal mucosal barrier of livestock and poultry, significantly reduce the irritation and damage of free ions to the intestines, improve intestinal health, and is suitable for peripartum stress sows and laying hens with sensitive intestines. The product of this invention is a fully water-soluble liquid system that is stable at room temperature. It does not separate or precipitate after 30 days and has a pH value of 5.0 to 7.5, which is close to the physiological pH of livestock and poultry intestines. It can be directly mixed into the drinking water system for large-scale addition or sprayed onto mixed feed. It solves the problems of easy grading and uneven mixing when mixing existing solid compound minerals with feed, as well as the problems of ordinary liquid minerals having no coating structure, poor stability, and easy precipitation. It is suitable for different breeding models of large-scale breeding groups and small and medium-sized farms. The product of this invention can increase the average birth weight of piglets by 7.9%, the survival rate of weaned piglets by 5.6% to 7.4%, and the feed intake of sows after farrowing by 6.8%. The incidence of postpartum stress is reduced from 22.3% to 7.6%, and the incidence of postpartum diarrhea is reduced from 16.5% to 4.3%, significantly alleviating peripartum stress and improving lactation performance. Commercial layer hen breeding trials show that the average egg production rate is increased by 3.5%, the relative eggshell strength is increased by about 9.3%, the proportion of broken eggs and soft-shelled eggs is reduced by 4.1%, the stability of the egg production cycle is significantly improved, and the eggshell quality is significantly improved. This indicates that the product of this invention can effectively improve the economic benefits of breeding sows and commercial layer hens during the peripartum period. Attached Figure Description

[0017] Figure 1 This is a comparison chart of the average daily feed intake of sows 7 days postpartum according to the present invention; Figure 2 This is a comparison chart of the average birth weight of piglets according to the present invention; Figure 3 This is a comparison chart of weaned piglet survival rates according to the present invention; Figure 4 This is a comparison chart of the incidence of stress and diarrhea in sows according to the present invention; Figure 5 This is a comparison chart of the total trace element excretion in sow feces according to the present invention; Figure 6 This is a comparison chart of the average egg production rate of the present invention; Figure 7 This invention provides a comparison of egg production quality indicators for laying hens. Figure 8 This invention provides a comparison of the average daily mortality rate of laying hens. Figure 9 This is a comparison chart of sow reproductive performance according to the present invention; Figure 10 This is a comparison chart of sow health and piglet growth indicators according to the present invention; Figure 11 This is a comparison chart of the egg production performance of high-producing hens according to the present invention; Figure 12 This is a comparison chart of egg quality indicators according to the present invention; Figure 13 This is a comparison chart of the health indicators of laying hens according to the present invention. Detailed Implementation

[0018] See attached document Figure 1-13 A polysaccharide-coated nano-liquid composite mineral, characterized in that it is composed of a nano-composite trace element core and a polysaccharide coating layer, and the whole is a water-soluble liquid system. By mass percentage, the raw material components are: 3%–15% complex trace elements, 2%–10% coated polysaccharides, 1%–5% cosolvent, and the balance being deionized water; The composite trace elements are a combination of two or more water-soluble inorganic salts from iron, zinc, copper, manganese, selenium, and cobalt. The coated polysaccharide is one or more of water-soluble plant polysaccharides and microbial polysaccharides.

[0019] Employing a core-shell structure of "nanocomposite trace element core + polysaccharide coating layer," water-soluble polysaccharides are used as the coating carrier to in-situ encapsulate nanoscale trace elements. On the one hand, the steric hindrance of the polysaccharide coating layer physically isolates different trace elements such as iron, zinc, copper, manganese, selenium, and cobalt, preventing ion antagonism and complexation precipitation when multiple metal ions coexist in aqueous solution, thus enabling each trace element to synergistically exert its supplementary effect. On the other hand, by limiting the ratio of composite trace elements, coating polysaccharides, and co-solvents, the product's effective ingredient content is ensured to be moderate, the system has good fluidity, and the supplementation effect is balanced with production and storage costs.

[0020] Furthermore, the polysaccharide-coated nano-liquid composite mineral is a nanoscale water-soluble liquid system with an average particle size of 20–100 nm, a pH value of 5.0–7.5, and exhibits no stratification or precipitation after 30 days of storage at room temperature. By using ultrasonic nano-processing, the particle size of the product is controlled within 20-100nm. The particles have a large specific surface area and high surface energy, which can significantly improve the dispersibility and solubility of trace elements in water. At the same time, the small nano-particle size is conducive to the adhesion, endocytosis and absorption of trace elements on the intestinal mucosa, greatly improving bioavailability. The pH value of the system is controlled at 5.0 to 7.5, which is close to the physiological pH of the livestock and poultry intestines. This avoids the stimulation and damage of strong acid and alkaline environments to the digestive tract mucosa, and also ensures the stability of the polysaccharide coating layer structure and prevents trace elements from being dehydrated and precipitated. The product showed no stratification or sedimentation after 30 days of storage at room temperature, indicating that it has good storage stability and shelf life, and can meet the long-term storage and continuous use needs of large-scale farming.

[0021] Furthermore, the water-soluble plant polysaccharide is one or more of the following: glucan, astragalus polysaccharide, wolfberry polysaccharide, seaweed polysaccharide, and pectin; The microbial polysaccharide is one or more of xanthan gum, yeast polysaccharide, and β-glucan; The plant polysaccharides and microbial polysaccharides mentioned above share the common characteristics of good water solubility, high biocompatibility, and excellent film-forming properties, and can form a uniform and stable coating layer on the surface of nano-trace elements; Among them, astragalus polysaccharides, wolfberry polysaccharides, yeast polysaccharides, and β-glucan themselves have biological activities such as enhancing the immunity of livestock and poultry, relieving stress, repairing intestinal mucosal damage, and promoting nutrient absorption. As coating materials, they can play a dual role of "coating carrier + functional component" at the same time, forming a synergistic effect with trace elements. They have significant conditioning and improvement effects on postpartum stress and decreased immunity in peripartum sows and sub-health status in laying hens during the egg-laying period.

[0022] Furthermore, the proportions of each component of the composite trace element are as follows: iron 10-30 parts, zinc 8-25 parts, copper 1-8 parts, manganese 5-20 parts, selenium 0.1-1 parts, and cobalt 0.1-0.8 parts; It was optimized through extensive screening experiments to meet the physiological needs of periparturient sows for reproduction, lactation, stress resistance, as well as the egg production and eggshell calcification of commercial laying hens. Among them, iron, zinc, copper and manganese are essential macro and micro elements for livestock and poultry, and they participate in key physiological processes such as hemoglobin synthesis, metalloenzyme formation, bone development and eggshell calcification, and are used in relatively large quantities. Although the amounts of selenium and cobalt added are small, they are indispensable for the body's antioxidant defense, immune regulation, and vitamin B12 synthesis. The components are formulated in the above-mentioned proportions by weight to avoid ion antagonism or potential toxicity caused by excessive addition of a single element, achieving synergistic utilization of multiple elements and balancing supplementation efficiency and safety.

[0023] Furthermore, the co-solvent is one or more of propylene glycol, glycerol, and anhydrous ethanol; Propylene glycol, glycerol, and anhydrous ethanol are all water-soluble cosolvents that can promote the uniform dispersion of nano-trace elements and polysaccharides in aqueous solutions, prevent the sedimentation and aggregation of active ingredients, and improve the dispersion stability of the system. Meanwhile, it has certain moisturizing, antibacterial and antiseptic effects, which helps to extend the shelf life of the product. In addition, the above-mentioned cosolvents all meet the hygiene and safety requirements of feed additives and can be safely used in livestock and poultry drinking water or feed additives.

[0024] A method for preparing a polysaccharide-coated nano-liquid composite mineral according to any one of the claims, characterized in that it comprises the following steps: Step 1: Preparation and Nano-Sizing of Trace Element Mother Solution: The water-soluble inorganic salts corresponding to the composite trace elements are added to deionized water in the order of iron salt, zinc salt, copper salt, manganese salt, selenium salt, and cobalt salt, and stirred until completely dissolved. Then, the solution is subjected to ultrasonic dispersion and nano-sizing treatment to obtain a nano-trace element mother solution. In Step 1, the water-soluble inorganic salts are added and stirred in the order of iron salt, zinc salt, copper salt, manganese salt, selenium salt, and cobalt salt to avoid excessively high local ion concentrations and mutual reactions leading to precipitation caused by the simultaneous addition of multiple salts, ensuring that each salt is fully and completely dissolved to form a homogeneous solution. Subsequently, ultrasonic dispersion and nano-sizing treatment is performed, using ultrasonic cavitation to break the particles to the nanoscale, providing a uniform nano-core for subsequent coating. Step 2: Polysaccharide swelling and dissolution: Add the coated polysaccharide to deionized water, heat in a water bath and stir to allow the polysaccharide to fully swell and completely dissolve, resulting in a polysaccharide solution. Step 2 involves heating the coated polysaccharide in a water bath to fully swell and dissolve it, resulting in a homogeneous, transparent polysaccharide solution with a certain viscosity, which serves as the coating carrier matrix. Step 3: In-situ coating at constant temperature: Keep the polysaccharide solution warm and stir. Add the nano-trace element mother liquor obtained in Step 1 to the polysaccharide solution at a uniform rate. After the addition is complete, continue stirring at a constant temperature to complete the polysaccharide coating and obtain the coating mixture. In Step 3, the nano-trace element mother liquor is added to the polysaccharide solution at a uniform rate. The uniform rate of addition can avoid particle agglomeration and incomplete coating caused by excessive local concentration. It can achieve uniform adsorption and coating of polysaccharide on nanoparticles and form a stable core-shell structure, i.e., in-situ coating at constant temperature. Step 4: Preparation and pH adjustment: Add a co-solvent to the coating mixture, stir and mix evenly, adjust the pH of the system to 5.0-7.5, add deionized water to make up the volume, stir and mix evenly. Adding a co-solvent in step 4 promotes the dispersion and stability of the system, and adjusting the pH to 5.0-7.5 takes into account both the physiological pH of the intestine and the stability of the system. Then add water to make up the volume to ensure the accurate concentration of the active ingredient. Step 5: Filtration and sterilization: Vacuum filtration and sterilization are performed using a 0.22μm aqueous microporous membrane. The filtrate is then filled to obtain the polysaccharide-coated nano-liquid composite mineral. Step 5 involves vacuum filtration and sterilization using a 0.22μm aqueous microporous membrane to remove microorganisms and any possible agglomerated particles, ensuring the product's hygiene, safety, and uniformity. Aseptic filling facilitates long-term storage and large-scale application.

[0025] Furthermore, in step 1, the stirring speed is 200–250 r / min, and the stirring time is 15–25 min; the ultrasonic power for ultrasonic dispersion and nano-dispersion is 200–300 W, using an intermittent mode (3 seconds of ultrasonication followed by a 2-second pause), with a total processing time of 20–40 min. In step 1, the stirring speed of 200–250 r / min and the stirring time of 15–25 min ensure complete dissolution of the inorganic salts without violent splashing; the intermittent ultrasonication mode of 200–300 W (3 seconds of ultrasonication followed by a 2-second pause) ensures sufficient nano-dispersion while avoiding localized overheating of the liquid and denaturation of trace element ions caused by continuous high-power ultrasonication. The total ultrasonication time of 20–40 min stably controls the particle size within the nanometer range; too short a time results in larger particle sizes, while too long a time easily leads to system aggregation. In step 2, the water bath heating temperature is 40-50℃, the stirring speed is 250-300 r / min, and the stirring time is 30-60 min. In step 2, the water bath temperature of 40-50℃ is the optimal swelling temperature for water-soluble polysaccharides. If the temperature is too low, the polysaccharides will not swell completely or dissolve evenly. If the temperature is too high, it will destroy the biological activity of the polysaccharides and lose their anti-stress and intestinal protection functions. In step 3, the polysaccharide solution is kept at a temperature of 35–45℃, the stirring speed is 300–350 r / min, and the dropping rate of the nano-trace element mother liquor is 8–12 mL / min. After the dropping is completed, the reaction is continued at a constant temperature and stirred for 40–70 min. In step 3, the dropping rate of 8–12 mL / min is the core parameter for achieving uniform monolayer coating. If the dropping rate is too fast, the local concentration will be too high, which will easily lead to particle agglomeration and incomplete coating. If the dropping rate is too slow, the production efficiency will be low and it will not be conducive to industrialization. The coating reaction temperature of 35–45℃ takes into account both the binding force between polysaccharide and nanoparticles and the activity of polysaccharide. In step 4, the co-solvent is stirred and mixed for 10-15 minutes, the pH of the system is adjusted to 5.0-7.5, deionized water is added to make up the volume and then stirred for 15 minutes. In step 4, the pH is adjusted to 5.0-7.5, which is close to the normal pH of the livestock and poultry intestines, while ensuring the stability of the polysaccharide structure and the absence of precipitation of trace elements.

[0026] Furthermore, in step 1, the iron salt is ferrous sulfate, the zinc salt is zinc sulfate, the copper salt is copper sulfate, the manganese salt is manganese sulfate, the selenium salt is sodium selenite, and the cobalt salt is cobalt chloride. Ferrous sulfate, zinc sulfate, copper sulfate, manganese sulfate, sodium selenite, and cobalt chloride are all food / feed grade water-soluble inorganic salts, which have the advantages of good water solubility, easy dissolution, readily available raw materials, and low production costs. They all meet the hygiene standards for feed additives and can be safely used for supplementing trace elements in livestock and poultry, ensuring both the effectiveness of supplementary feeding and economic efficiency.

[0027] Furthermore, steps 2 to 4 are conducted entirely in a cleanroom with an ambient temperature of 20–28°C and a relative humidity of 40%–65%. Core processes such as dissolution, coating, and preparation are carried out within this cleanroom (temperature 20–28°C, relative humidity 40%–65%). This approach avoids the impact of temperature and humidity fluctuations on the ultrasonic nano-sizing effect, polysaccharide swelling and dissolution, and the coating reaction process, ensuring consistent product quality between batches. It also effectively reduces contamination of the system by external microorganisms and dust impurities. Combined with the filtration and sterilization process in step 5, this ensures that the product's hygiene and quality meet the safety requirements for livestock medication.

[0028] The application of any one of the polysaccharide-coated nano-liquid composite minerals in livestock and poultry farming is characterized in that the application targets are periparturient sows and / or commercial laying hens, and the application method is to add it to drinking water or spray it onto the feed surface for mixing. During the peripartum period, sows are in the late stages of pregnancy and lactation. Their metabolism is vigorous, their demand for trace elements is high, and they are in a stage of physiological stress sensitivity. Adding this product to drinking water or spraying it on feed can effectively alleviate postpartum stress, improve lactation performance, and increase the birth weight and weaning survival rate of piglets. Commercial laying hens have a high demand for trace elements during their peak egg-laying period, and their absorption and utilization directly determine egg production rate and eggshell quality. Supplementing with this product through drinking water or spraying can improve egg production rate, enhance eggshell strength and quality, and extend the stability of the egg-laying cycle. This product is a fully water-soluble liquid formulation, which can be directly mixed into the drinking water system for large-scale addition, or sprayed onto mixed feed. It is convenient to use, provides precise dosage, and is suitable for different farming models of large-scale breeding groups and small and medium-sized farms. Example 1

[0029] This embodiment provides a polysaccharide-coated nano-liquid composite mineral with the following formula (by mass percentage): 8% composite trace elements, 5% astragalus polysaccharide, 3% glycerol, and 84% deionized water; wherein the composite trace elements are, by mass, 20 parts iron, 15 parts zinc, 3 parts copper, 10 parts manganese, 0.3 parts selenium, and 0.2 parts cobalt.

[0030] The preparation process is as follows: (1) Dissolution and ultrasonic nano-sizing of trace elements: Take the amount of deionized water specified in the formula, and add ferrous sulfate, zinc sulfate, copper sulfate, manganese sulfate, sodium selenite and cobalt chloride in sequence at room temperature. Stir at 220 r / min for 20 min until completely dissolved. Turn on the ultrasonic dispersion device, ultrasonic power 250 W, intermittent mode (ultrasound for 3 s, pause for 2 s), total ultrasonic time 30 min, to obtain a uniform nano-trace element mother liquor. The average particle size was 45 nm as detected by DLS. (2) Swelling and dissolution of Astragalus polysaccharide: Take the corresponding deionized water, heat it to 45°C in a water bath, add Astragalus polysaccharide, stir at 280 r / min and keep the temperature constant for 45 min to obtain a transparent and homogeneous polysaccharide solution; (3) Constant temperature in situ coating: The polysaccharide solution was kept at 40°C and the stirring speed was 320 r / min. The nano-trace element mother liquor was added dropwise at a uniform rate of 10 mL / min. After the addition was completed, the constant temperature stirring was continued for 55 min to complete the polysaccharide coating. (4) Preparation and pH adjustment: Add the amount of glycerol specified in the formula, stir for 12 min to mix evenly, adjust the pH of the system to 6.2 with food-grade dilute hydrochloric acid / sodium hydroxide, add water to make up the volume, and stir for 15 min; (5) Filtration and sterilization: Vacuum filtration and sterilization were carried out using a 0.22μm water-based microporous filter membrane, followed by aseptic filling. Finished product testing: Average particle size 45nm, pH 6.2, no stratification or sedimentation after 60 days of sealed storage at room temperature. Breeding application trial: 60 bi-crossbred peripartum sows (95 days of gestation, weight 220±12kg) and 2000 commercial Lohmann Brown laying hens (28 weeks of age, peak egg production) were randomly divided into a blank group, a control group (equal dose of conventional inorganic trace elements added to drinking water), and an experimental group (the product of this embodiment was added to drinking water, with a daily supplement of compound trace elements of 120mg / kg body weight; laying hens had 80mg / L of drinking water mixed throughout the day). The trial period for sows was 40 days (from 95 days of gestation to 21 days postpartum weaning), and the trial period for laying hens was 90 days. (1) Peripartum sow production and health indicators: like Figure 1 As shown, the average daily feed intake of sows in the experimental group was 4.81 kg 7 days postpartum, significantly higher than the 4.35 kg in the control group (P < 0.05), representing a 10.6% increase compared to the control group. The control group's intake was 4.12 kg. This indicates that the product in this embodiment, when added to drinking water, can effectively alleviate postpartum stress in sows, promote postpartum feed intake recovery, and ensure adequate nutrient intake during lactation and proper nursing of piglets.

[0031] like Figure 2 As shown, the average birth weight of piglets in the experimental group was 1.36 kg, which was 7.9% higher than that of the control group (1.26 kg), and the difference was highly significant (P < 0.01); the average birth weight of the control group was 1.21 kg. This indicates that nano-sizing and polysaccharide coating significantly improved the absorption and utilization rate of trace elements, enabling sows to provide more sufficient trace elements to the fetus in late pregnancy, thus promoting intrauterine growth and development of the fetus.

[0032] like Figure 3 As shown, the survival rate of weaned piglets in the experimental group on day 21 was 93.1%, an increase of 7.4% compared to 86.7% in the control group and 82.4% in the blank group. The milk of sows during the peripartum period contains sufficient trace elements and has improved lactation performance, allowing piglets to obtain more comprehensive nutrition from their mother's milk, resulting in enhanced physical condition and a significantly higher survival rate.

[0033] like Figure 4As shown, the peripartum stress rate in the experimental group decreased significantly from 22.3% in the control group to 7.6%, and the postpartum diarrhea rate decreased from 16.5% in the control group to 4.3%, compared to 28.5% and 19.2% in the blank group, respectively. The polysaccharide coating layer can protect the intestinal mucosa and neutralize the acidic stimulation of free metal ions. At the same time, Astragalus polysaccharides have the biological activity of alleviating stress. The two synergistically reduced the occurrence of peripartum stress and postpartum symptoms such as agalactia, lying down, and diarrhea.

[0034] like Figure 5 As shown, the total trace element excretion in the feces of sows in the experimental group was 428 mg / d, a decrease of 61.9% compared to 1126 mg / d in the control group. The intestinal absorption and utilization rate of trace elements was greater than 60%, which is far higher than the 10%–25% of traditional inorganic minerals. The targeted delivery of trace elements by combining nanoparticle size with polysaccharide coating significantly reduces the excretion of trace elements in feces, thereby reducing the pollution of soil and water bodies by heavy metals such as copper, zinc, and iron from the source, making it green and environmentally friendly.

[0035] like Figure 6 As shown, the average egg production rate of the experimental group was 92.9%, which was 3.5% higher than that of the control group (89.4%), showing a significant difference. The blank group had an average egg production rate of 87.2%. The increased absorption and utilization of trace elements such as iron, zinc, and manganese provided sufficient raw materials for follicle development and ovulation, resulting in a significant increase in egg production rate.

[0036] like Figure 7 As shown, the proportion of broken and soft-shelled eggs in the experimental group was 2.2%, a decrease of 4.1% compared to 6.3% in the control group; the eggshell strength was 38.5 N / cm², significantly higher than the 34.1 N / cm² in the control group, while the values ​​in the blank groups were 7.8% and 32.6 N / cm², respectively. Sufficient absorption of trace elements promoted eggshell calcification and deposition, significantly improved eggshell hardness, greatly reduced the proportion of broken and soft-shelled eggs, and increased the marketable yield of eggs.

[0037] like Figure 8 As shown, the average daily mortality rate of laying hens in the experimental group was 0.48‰, significantly lower than the 1.15‰ in the control group and 1.42‰ in the blank group. Polysaccharides enhance the immunity of laying hens, improve gut health, and, combined with the efficient utilization of trace elements, reduce the risk of mortality during peak egg production due to sub-health conditions.

[0038] In summary, the product of Example 1 showed significant application effects in both peripartum sows and commercial laying hens, verifying the outstanding advantages of the polysaccharide-coated nano-liquid composite mineral of the present invention in improving the bioavailability of trace elements, alleviating stress, and improving production performance and eggshell quality. Example 2

[0039] This embodiment provides a polysaccharide-coated nano-liquid composite mineral with the following formula (mass percentage): 6% composite trace elements, 8% yeast polysaccharide + seaweed polysaccharide (1:1 composite), 2% propylene glycol, and 84% deionized water; wherein the composite trace elements, by mass, are: 25 parts iron, 12 parts zinc, 2 parts copper, 8 parts manganese, 0.5 parts selenium, and 0.3 parts cobalt. The preparation process is as follows: (1) Trace element dissolution and ultrasonic nano-sizing: stirring speed 200r / min, stirring for 25min, ultrasonic power 220W, intermittent mode (ultrasound 3s, pause 2s), total ultrasonic time 25min, to obtain nano-mother liquor with an average particle size of 38nm. (2) Swelling and dissolution of complex polysaccharides: water bath temperature 42℃, stirring speed 260r / min, stirring for 50min; (3) In-situ coating at constant temperature: the temperature is 38℃, the stirring speed is 300r / min, the dropping rate is 9mL / min, and the constant temperature stirring is carried out for 60min after the dropping is completed; (4) Preparation and pH adjustment: Add propylene glycol and stir for 10 min, adjust the pH to 6.5, add water to make up the volume, and stir for 15 min; (5) Filtration and sterilization: Vacuum filtration using a 0.22μm water-based filter membrane, followed by aseptic filling. Animal husbandry application trial: Forty-five Landrace × Large White sows in late gestation (90 days of gestation) were randomly divided into a blank group, a control group (with equal doses of conventional inorganic trace elements added to drinking water), and an experimental group (with the product of this embodiment added to drinking water, and the amount of trace elements added was consistent with the control group), with 15 sows in each group. The trial period was 45 days (from 90 days of gestation to 28 days of weaning for slaughter). This was a specific reproductive trial conducted only on peripartum sows.

[0040] like Figure 9 As shown, the average daily feed intake of sows in the experimental group was 4.58 kg 10 days postpartum, an increase of 6.8% compared to 4.29 kg in the control group (P < 0.05), and 4.05 kg in the blank group. The survival rate of weaned piglets on day 28 was 91.5%, an increase of 5.6% compared to 85.9% in the control group and 81.3% in the blank group. The coating with seaweed polysaccharides and yeast polysaccharides effectively reduced the stimulation of free metal ions on the sow's intestines, accelerated postpartum feed intake recovery, increased milk production, and significantly improved the survival rate of weaned piglets.

[0041] like Figure 10 As shown, the incidence of agalactia syndrome in sows in the experimental group was 6.7%, which was significantly lower than 20.0% in the control group and 26.7% in the blank group; the average weaning weight of piglets was 7.04 kg, which was significantly higher than 6.61 kg in the control group and 6.25 kg in the blank group; the intestinal mucosal damage score (0-5 points, with higher scores indicating more severe damage) of sows in the experimental group was 1.1 points, which was significantly lower than 2.9 points in the control group and 3.4 points in the blank group.

[0042] Yeast polysaccharides can enhance local immunity in the mammary glands and promote lactation. Seaweed polysaccharides synergistically repair the intestinal mucosa and eliminate metal ion stimulation, thus improving the lactation performance and restoring intestinal health in sows. Piglets obtain more trace elements from sow's milk, resulting in simultaneous increases in weaning weight and survival rate. Example 2 shows that using a complex of polysaccharides such as yeast polysaccharides and seaweed polysaccharides as coating materials can achieve a synergistic effect of intestinal protection and lactation improvement in peripartum sows, further verifying the promoting effect of polysaccharide selection on breeding outcomes in this invention. Example 3

[0043] This embodiment provides a polysaccharide-coated nano-liquid composite mineral with the following formulation (by mass percentage): 12% composite trace elements, 4% xanthan gum + pectin (1:1 composite), 4% glycerol + propylene glycol (1:1 composite), and 80% deionized water; wherein the composite trace elements, by mass, are: 12 parts iron, 22 parts zinc, 4 parts copper, 15 parts manganese, 0.2 parts selenium, and 0.1 parts cobalt. The preparation process is as follows: (1) Trace element dissolution and ultrasonic nano-sizing: stirring speed 240r / min, stirring for 18min, ultrasonic power 280W, intermittent mode (ultrasound 3s, pause 2s), total ultrasonic duration 35min, average particle size 62nm; (2) Swelling and dissolution of complex polysaccharides: water bath temperature 48℃, stirring speed 290r / min, stirring for 35min; (3) In-situ coating at constant temperature: the temperature is 42℃, the stirring speed is 330r / min, the dropping rate is 11mL / min, and the constant temperature stirring is performed for 45min after the dropping is completed; (4) Preparation and pH adjustment: Add compound co-solvent and stir for 14 min, adjust pH to 5.8, add water to make up the volume, and stir for 15 min; (5) Filtration and sterilization: Vacuum filtration using a 0.22μm water-based filter membrane, followed by aseptic filling. Aquaculture application trial: 1500 Hy-Line Brown high-producing laying hens (at stable peak egg production at 32 weeks of age) were randomly divided into a blank group, a control group (with inorganic mineral supplementation in drinking water of equal trace element content), and an experimental group (with the product of this embodiment added to drinking water), with 500 hens in each group. The trial period was 90 days, with long-term egg production observation. Standardized cage rearing was implemented, with uninterrupted water supply and product addition throughout the process.

[0044] like Figure 11As shown, the average egg production rate of the experimental group throughout the entire production cycle was 91.8%, significantly higher than the 88.7% of the control group and 86.5% of the blank group. There was no significant decline in egg production throughout the entire production cycle, indicating significantly improved stability. The eggshell strength of the experimental group was 36.3 N / cm², an absolute increase of 3.1 N / cm² and a relative increase of approximately 9.3% compared to the 33.2 N / cm² of the control group, with a highly significant difference (P < 0.01). The blank group's eggshell strength was 31.8 N / cm². With long-term feeding, trace element absorption was stable, calcification deposition was sufficient, and both egg production performance and eggshell quality were effectively guaranteed.

[0045] like Figure 12 As shown, the total proportion of soft-shelled and cracked eggs in the experimental group was 2.6%, significantly lower than the 6.7% in the control group and 8.1% in the blank group; the average weight of a single egg was 59.1g, higher than the 57.8g in the control group and 57.2g in the blank group. The efficient utilization of trace elements (especially zinc and manganese) promotes eggshell calcification, ensures sufficient nutrient deposition, significantly reduces the proportion of soft-shelled and cracked eggs, increases the weight of a single egg, and enhances the commercial value of the eggs.

[0046] like Figure 13 As shown, the intestinal diarrhea rate of laying hens in the experimental group was 2.1%, significantly lower than the 8.3% in the control group and 10.6% in the blank group; the cumulative mortality rate at 90 days was 3.6‰, significantly lower than the 10.4‰ in the control group and 13.8‰ in the blank group. Pectin and xanthan gum coating can protect the intestines and reduce the stimulation of the intestines by free copper and zinc ions. Combined with the immune-enhancing effect of polysaccharides, this significantly reduced intestinal diseases and sub-health mortality during the laying period, extending the effective laying cycle of laying hens.

[0047] Example 3 shows that, under 90-day long-term feeding conditions for high-producing laying hens, the product of this example can achieve comprehensive improvement in egg production performance, eggshell quality and body health, verifying the long-term application value of the product of this invention in large-scale commercial laying hen farming.

[0048] In summary, the breeding experiment results of the above embodiments show that the polysaccharide-coated nano-liquid composite mineral of the present invention, through the nano-core + polysaccharide coating structure, significantly improves the bioavailability and intestinal absorption efficiency of trace elements such as iron, zinc, copper, manganese, selenium, and cobalt, effectively eliminates inter-element antagonism, reduces intestinal irritation, alleviates postpartum stress in peripartum sows, significantly improves reproductive and lactation performance, and significantly enhances the egg production rate, eggshell strength, and laying cycle stability of commercial laying hens. At the same time, it greatly reduces the excretion of trace elements in feces, and has the outstanding advantages of efficient supplementation and green environmental protection.

[0049] The above-described embodiments are merely illustrative of certain implementations of the present invention, and are described in a relatively specific and detailed manner. However, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.

Claims

1. A polysaccharide-coated nano-liquid composite mineral, characterized in that, It consists of a nanocomposite trace element core and a polysaccharide coating layer, and the whole is a water-soluble liquid system; By mass percentage, the raw material components are: 3%–15% complex trace elements, 2%–10% coated polysaccharides, 1%–5% cosolvent, and the balance being deionized water; The composite trace elements are a combination of two or more water-soluble inorganic salts from iron, zinc, copper, manganese, selenium, and cobalt. The coated polysaccharide is one or more of water-soluble plant polysaccharides and microbial polysaccharides.

2. The polysaccharide-coated nano-liquid composite mineral according to claim 1, characterized in that: The polysaccharide-coated nano-liquid composite mineral is a nanoscale water-soluble liquid system with an average particle size of 20–100 nm and a pH value of 5.0–7.

5. It does not separate or precipitate after 30 days of storage at room temperature.

3. The polysaccharide-coated nano-liquid composite mineral according to claim 1, characterized in that: The water-soluble plant polysaccharides are one or more of the following: glucan, astragalus polysaccharide, wolfberry polysaccharide, seaweed polysaccharide, and pectin; The microbial polysaccharide is one or more of xanthan gum, yeast polysaccharide, and β-glucan.

4. The polysaccharide-coated nano-liquid composite mineral according to claim 1, characterized in that: The proportions of each component of the composite trace element are as follows: 10-30 parts iron, 8-25 parts zinc, 1-8 parts copper, 5-20 parts manganese, 0.1-1 parts selenium, and 0.1-0.8 parts cobalt.

5. The polysaccharide-coated nano-liquid composite mineral according to claim 1, characterized in that: The co-solvent is one or more of propylene glycol, glycerol, and anhydrous ethanol.

6. A method for preparing the polysaccharide-coated nano-liquid composite mineral according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Preparation and nano-sizing of trace element mother liquor: The water-soluble inorganic salts corresponding to the composite trace elements are added to deionized water in the order of iron salt, zinc salt, copper salt, manganese salt, selenium salt and cobalt salt, stirred until completely dissolved, and then subjected to ultrasonic dispersion and nano-sizing treatment to obtain nano-trace element mother liquor. Step 2: Polysaccharide swelling and dissolution: Add the coated polysaccharide to deionized water, heat in a water bath and stir to allow the polysaccharide to fully swell and completely dissolve, resulting in a polysaccharide solution; Step 3: In-situ coating at constant temperature: Keep the polysaccharide solution at a constant temperature and keep stirring. Add the nano-trace element mother liquor obtained in Step 1 to the polysaccharide solution at a constant rate. After the addition is complete, continue stirring at a constant temperature to complete the polysaccharide coating and obtain the coated mixture. Step 4: Preparation and pH adjustment: Add a co-solvent to the coating mixture, stir and mix evenly, adjust the pH of the system to 5.0-7.5, add deionized water to make up the volume, and stir and mix evenly; Step 5: Filtration and sterilization: Vacuum filtration and sterilization are performed using a 0.22μm aqueous microporous filter membrane. The filtrate is then filled into containers to obtain the polysaccharide-coated nano-liquid composite mineral.

7. The preparation method according to claim 6, characterized in that, In step 1, the stirring speed is 200-250 r / min and the stirring time is 15-25 min; the ultrasonic power for ultrasonic dispersion and nano-processing is 200-300 W, and the intermittent mode is adopted, with ultrasonication for 3 seconds and pause for 2 seconds, and the total processing time is 20-40 min. In step 2, the water bath heating temperature is 40-50℃, the stirring speed is 250-300 r / min, and the stirring time is 30-60 min; In step 3, the polysaccharide solution is kept at a temperature of 35-45℃, the stirring speed is 300-350 r / min, the dropping rate of the nano-trace element mother liquor is 8-12 mL / min, and the reaction is continued at a constant temperature for 40-70 min after the dropping is completed. In step 4, the co-solvent is stirred and mixed for 10-15 minutes, the pH of the system is adjusted to 5.0-7.5, deionized water is added to make up the volume, and then stirred for 15 minutes.

8. The preparation method according to claim 6, characterized in that, In step 1, the iron salt is ferrous sulfate, the zinc salt is zinc sulfate, the copper salt is copper sulfate, the manganese salt is manganese sulfate, the selenium salt is sodium selenite, and the cobalt salt is cobalt chloride.

9. The preparation method according to claim 6, characterized in that, Steps 2 through 4 are carried out entirely in a cleanroom with an ambient temperature of 20–28°C and a relative humidity of 40%–65%.

10. The application of the polysaccharide-coated nano-liquid composite mineral according to any one of claims 1-5 in livestock and poultry farming, characterized in that, The product is intended for peripartum sows and / or commercial laying hens, and is applied by adding it to drinking water or spraying it onto the feed surface.